2014
DOI: 10.1097/sla.0000000000000314
|View full text |Cite
|
Sign up to set email alerts
|

It's Big Surgery

Abstract: Objective To identify the processes surgeons use to establish patient buy-in to postoperative treatments. Background Surgeons generally believe they confirm the patient's commitment to an operation and all ensuing postoperative care, before surgery. How surgeons get buy-in and whether patients participate in this agreement is unknown. Methods We used purposive sampling to identify three surgeons from different subspecialties who routinely perform high-risk operations at each of three distinct medical cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…10,23,24 We also interviewed patients before (n=34) and after (n=27) surgery. We used an inductive coding strategy and deliberative adjudication process among researchers to support higher-level analysis whereby codes were expanded and refined to capture phenomena present in the data.…”
Section: Methodsmentioning
confidence: 99%
“…10,23,24 We also interviewed patients before (n=34) and after (n=27) surgery. We used an inductive coding strategy and deliberative adjudication process among researchers to support higher-level analysis whereby codes were expanded and refined to capture phenomena present in the data.…”
Section: Methodsmentioning
confidence: 99%
“…6-8 Furthermore, surgeons' conversations are framed by the structure of informed consent which functions poorly as a vehicle for decision making. 9 Although shared decision making holds promise for improving high-stakes clinical decision making by aligning patients' values with the appropriate treatment choice, contemporary efforts to improve shared decision making between patients and surgeons have focused on the out patient setting. 10, 11 …”
Section: Introductionmentioning
confidence: 99%
“…7 In a previous study of preoperative conversations, it was observed that surgeons assert a profound perception of “agency” or personal responsibility for the patient’s operative outcome, particularly survival. 8 This responsibility, embedded in surgical culture, may motivate the surgeon’s actions when patients require prolonged postoperative life-sustaining treatment.…”
Section: Introductionmentioning
confidence: 99%